Chemical properties and sensory characteristics of wild boar meat (Sus scrofa scrofa) fed with acorns (Quercus robur) - Flores Ahumada , Paulina G; Morales Pavez , Rodrigo; Skewes Ramm , Oscar (Revista de Producción Animal, 2023)
Backround: The wild boar (Sus scrofa scrofa) has favourable meat characteristics compared to the domestic pig particularly regarding the fat and cholesterol content. The present study aimed to determine whether the meat of wild boar fed with 20% or 40% acorns in their diet had different chemical properties and sensory meat characteristics.Methods: A group of six wild boar (Sus scrofa s.) with an initial live weight of 40 kg, received fresh whole Quercus robur acorns at 20% w/w of their daily feedstuff for 60 days, a second group received 40% w/w and a third group consumed commercial feed without acorns (control group). Proximal chemical analysis was performed on the feedstuff, acorns, and meat. Fatty acids and cholesterol in the Longissimus lumborum muscle were measured via gas chromatography.Results: The meat from the control fatty acid group had a higher composition of C16: 0 fatty acids and cholesterol, and also had a lower proportion of monounsaturated and polyunsaturated fatty acids, and of the n6: n3, P/S ratio, than the acorn-fed wild boar groups.Conclusions: The meat of wild board fed with acorn had better characteristics in terms of nutritional factors such as the level of monounsaturated fatty acids, polyunsaturated fatty acids, cholesterol, and sensory characteristics.Key words: animal nutrition; animal feed; essential fatty acids; food composition; meat industry (Source: UNBIS)